2017
DOI: 10.1097/aap.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Diskitis, Osteomyelitis, Spinal Epidural Abscess, Meningitis, and Endocarditis Following Sacroiliac Joint Injection for the Treatment of Low-Back Pain in a Patient on Therapy for Hepatitis C Virus

Abstract: Immunocompromised patients should be identified prior to treatment, and the small possibility of devastating complications should be thoughtfully weighed against the potential benefit of the procedure. Conservative management should be maximized initially, and if a procedure is done, strict asepsis must be maintained. Prophylaxis for S. aureus should be considered for immunocompromised patients undergoing interventional spine procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Overall, no major complications were reported in this systematic review, even though the literature largely documented the potential drawbacks of intraarticular steroid and anesthetic injections, with the risk of inducing local chondrolysis and osteoporosis, and, in case of surgery, of increased post-operative pain scores [36][37][38][39]. Local corticosteroids injections can lead also to systemic consequences by causing immunosuppression: infection diseases, Cushing's syndrome, weight gain, fluid retention, mood disturbances, and gastrointestinal upset [28].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, no major complications were reported in this systematic review, even though the literature largely documented the potential drawbacks of intraarticular steroid and anesthetic injections, with the risk of inducing local chondrolysis and osteoporosis, and, in case of surgery, of increased post-operative pain scores [36][37][38][39]. Local corticosteroids injections can lead also to systemic consequences by causing immunosuppression: infection diseases, Cushing's syndrome, weight gain, fluid retention, mood disturbances, and gastrointestinal upset [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 30-50% of adults are colonized with MRSA though totally asymptomatic, therefore screening programs (e.g., nasal swabs, skin swabs) are crucial to identify patients at higher risk of MRSA invasive infection [6,63]. As most MRSA invasive infections occur in patients without a history of MRSA colonization, besides in patients being colonized with MRSA, prophylaxis for SA should be carefully evaluated in every immunocompromised patient undergoing neurosurgery [64,65]. Time is a critical issue: screening should be performed as close to the operation date as possible, but in time to perform decolonization and/or preoperative prophylaxis.…”
Section: Prevention and Prophylaxismentioning
confidence: 99%
“…More serious reactions are rare . There is a case report of joint infection of the SIJ following intra‐articular injection, as well as a case of spinal epidural abscess, meningitis, and endocarditis in an immunosuppressed patient . Research has shown that radiation exposure is low with fluoroscopically guided injections .…”
Section: Summary Of the Published Literaturementioning
confidence: 99%
“…47,48 There is a case report of joint infection of the SIJ following intraarticular injection, 49 as well as a case of spinal epidural abscess, meningitis, and endocarditis in an immunosuppressed patient. 50 Research has shown that radiation exposure is low with fluoroscopically guided injections. [51][52][53] However, the effects of chronic exposure to fluoroscopy operators over time, at the individual radiation dose exposure rate demonstrated by SIJ studies, have not been reported.…”
Section: Adverse Eventsmentioning
confidence: 99%